Optimal Consumption and Investment with Capital Gains Taxes - Dammon, Robert M.; Spatt, Chester S.; Zhang, Harold H. (Review of Financial Studies, 2001)
This article characterizes optimal dynamic consumption and portfolio decisions in the presence of capital gains taxes and short-sale restrictions. The optimal decisions are a function of the investor’s age, initial portfolio holdings, and tax basis. Our results capture the trade-off between the diversification benefits and tax costs of trading over an investor’s lifetime. The incentive to rediversify the portfolio is inversely related to the size of the embedded gain and investor’s age. Contrary to standard financial advice, the optimal equity holding increases well into an investor’s lifetime in our model due to the forgiveness of capital gains taxes at death.